ANALISA KEANDALAN JARINGAN DISTRIBUSI 20 KV MENGGUNAKAN METODE EMEA (FAILURE MODE AND EFFECT ANALISYS) PADA PT.PLN (PERSERO) CABANG MEDAN - Muhammad Adam (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
In this time PT,PLN (persero) strive the make-up of service of requirement of electrics energi to society. With exixtence of distribution system reliability analysis,can know how quality of from distribution system looked into from some kinds souce of troublr.